THE USE OF TIKTOK APPLICATIONS IN LEARNING ENGLISH AT THE NINTH GRADE STUDENTS OF SMPN 1 BURU - Rahman, Sakinah Nur; Setiadi, Muhammad Astrianto; Hambali, Uyunnasirah (English Language Teaching Methodology, 2024)
This study aims to find out whether the use of TikTok application is effective in learning English at the ninth grade students of SMPN 1 Buru in the academic year 2022/2023. The type of research used is pre-experimental research using one class. The population in this study consisted of all grade IX students. The sample in this study was class IX.3 which consisted of 30 students. The sampling technique in this study used purposive sampling. This research was conducted for 6 meetings. The instrument used in this study is a prononciation test which is carried out on the pre test and post test. The data was processed using SPSS application. Based on the results of data analysis and discussion that has been put forward it can concluded that after applying TikTok in teaching english can improve students pronounciation in class IX.3 at SMPN 1 BURU. This is evidenced by the results of the students' scores. It is shown from the mean or average score of the students that there is an increase of . The students’ pre-test was gotten 44.67 and the students’ post-test was gotten 79,83. the post-test score shows higher score than the pre-test. In addition, the hypothesis testing is evidenced by t-test value, where the t-test (41.255) score is higher than the t-table (2.045) score. That means, that Ho is rejected and Ha is approved. As a result, the hypothesis of this study, that using TikTok has a significant effect on students' pronunciation in SMPN 1 BURU, is accepted.